2013
DOI: 10.1002/jrs.4332
|View full text |Cite
|
Sign up to set email alerts
|

Studies on paint cross sections of a glass painting by using FT‐IR and Raman microspectroscopy supported by univariate and hierarchical cluster analyses

Abstract: Fourier transform infrared (FT‐IR) and Raman spectroscopy is used for the non‐destructive analysis of painting materials and ageing compounds in micrometric cross sections of a glass painting. The combination of both techniques in conjunction with imaging/mapping function provides the spatial distribution of chemical components identified in vibrational spectra. The aim of our work is to show the applicability of the FT‐Raman mapping technique in the detection of painting materials. We also compare Raman infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
(100 reference statements)
0
9
0
1
Order By: Relevance
“…This approach in processing IR and Raman images was introduced by us. 18 Vis-Raman spectra were collected by using a Raman microspectrometer WITec Alpha 300, equipped with an air cooled solid state laser operating at 532 nm and a CCD detector. A microscope was coupled with a laser and a spectrograph via a single mode optical fiber with a diameter of 50 µm.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…This approach in processing IR and Raman images was introduced by us. 18 Vis-Raman spectra were collected by using a Raman microspectrometer WITec Alpha 300, equipped with an air cooled solid state laser operating at 532 nm and a CCD detector. A microscope was coupled with a laser and a spectrograph via a single mode optical fiber with a diameter of 50 µm.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Raman mapping using a conventional motorised stage is used in the cultural heritage field on micro-samples and cross-sections of samples such as paint layers (in favourable cases where fluorescence is not a complete impediment to analysis) [94,153,287], calcium oxalates layers deposited on the surfaces of monuments as deterioration products or as intentional mineral consolidation treatments [92,93], iron corrosion layers [210], and other corrosion products of archaeological metal objects [18] or porcelain cards [116]. When it comes to in situ analyses, unless the object fits under the microscope and can be securely held on the motorised stage, which is not often the case, different approaches must be considered.…”
Section: Mapping and Wide-field Raman Spectroscopymentioning
confidence: 99%
“…By far though, the most highly used approaches rely on PCA, HCA and PLS-DA for materials classification in many contexts: to identify and discriminate pigments [214,223,287,297], dyes [121] and inks [238]; to characterise organic media [105,[215][216][217]229] and metallic soaps [226]; and in the related domains of forensic science [123] for the analysis of industrial paints [212]. In essence, data reduction processes using PCA for the automatic identification of pigments in works of art work by first performing data pre-treatment of a reference spectral library, including spectral range selection, baseline subtraction, linear interpolation, and intensity normalisation.…”
Section: Materials Identification and Discriminationmentioning
confidence: 99%
“…The combination of these methods demonstrates their utility for the study on the paint cross sections of the works of art. [189] Tomasini and coworkers identified atacamite as a natural pigment in a South American colonial polychrome sculpture from the late XVI century. They found that atacamite was used as the green pigment and identified it for the first time as a mineral pigment in a colonial sculpture made in the Viceroyalty of Peru.…”
Section: Coherent Anti-stokes Raman Spectroscopymentioning
confidence: 99%
“…Staniszewska et a l. studied paint cross sections of a glass painting by using FT‐IR and Raman microspectroscopy supported by univariate and hierarchical cluster analyses. The combination of these methods demonstrates their utility for the study on the paint cross sections of the works of art . Tomasini and coworkers identified atacamite as a natural pigment in a South American colonial polychrome sculpture from the late XVI century.…”
Section: Introductionmentioning
confidence: 99%